Juridical Implications of the Imposition of Substitute Imprisonment under the Attorney General Guideline - Muhammad Fahmi Abdillah; Prija Djatmika; Yuliati (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Corruption as an extraordinary crime causes state financial losses that have not been optimally recovered, particularly because convicted persons tend to choose substitute imprisonment rather than paying compensation. Although this mechanism has been regulated under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, its implementation has resulted in a significant accumulation of unrecovered state losses. The issuance of Attorney General Guideline Number 1 of 2019 was intended to serve as a technical guideline for prosecution; however, it continues to raise juridical issues. This study aims to analyze the juridical implications of the implementation of the guideline and to formulate an ideal regulatory framework. The research employs a normative juridical method using statutory, conceptual, and comparative approaches, which are analyzed prescriptively. The findings indicate the existence of legal uncertainty due to the absence of clear parameters for determining substitute imprisonment, low effectiveness resulting from its alternative nature, weak coercive force, and inconsistency in prosecutorial discretion. Therefore, a reformulation of the regulation is necessary by positioning compensation payment as a mandatory and cumulative sanction in order to optimize the recovery of state financial losses and strengthen legal certainty and consistency in prosecution.